Dekorasi Pelaminan Karya Kemahen Art Decoration Ditinjau Dari Prinsip-Prinsip Desain - Dwi Syahfitri; Saragi Daulat (Institut Seni Indonesia Padang Panjang, 2023)
ABSTRACTThe art of decoration is the art of designing, arranging objects, shapes, rooms and other objects with the aim of beautifying and beautifying the visual appearance of the object to be decorated. Relating to the art of decoration, especially the decoration of the aisle. In this era, many wedding receptions were seen as reflection of the culture of society. Changes in wedding decoration design models can characterize changes in modern society’s culture. With the aim of knowing a good form of wedding decoration, to find out the suitability of the application of the layout of the decoration that is used as a decoration element, to find out the arrangement of properties, as well as the color theme used in the elements of the wedding decoration. Observing these conditions the outhor tries to analyze with descriptive analysis methods and interviews with one off the wedding organizers in the city of Medan. Based on the results of the research, it can be concluded that the art decoration camp applies design priciples to decoration works of the several decorations, thera are those who apply all design principles, and there are those who apply only a few principles. The shapes used mostly use geometric shapes, The layout of the décor elements is laid out according to design principles. As well as variations in the form of decoration tailored to the requests of each client. However, many clients also ask for the type of decoration that is already provided by the vendor.Keywords: decoration, aisle, analysis, principle, design ABSTRAK Seni dekorasi adalah seni merancang, menata benda, bentuk, ruangan, dan benda lainnya dengan tujuan mempercantik dan memperindah tampilan visual dari benda yang akan dihias. Berkaitan dengan seni dekorasi, terkhususnya dekorasi pelaminan. Pada era ini resepsi pernikahan banyak dilihat sebagai refleksi kebudayaan masyarakat. Perubahan model desain dekorasi pernikahan dapat mencirikan perubahan dalam kebudayaan masyarakat yang modern. Dengan tujuan mengetahui bentuk dekorasi pernikahan yang baik, untuk mengetahui kesesuaian penerapan tata letak hiasan yang dijadikan sebagai elemen dekorasi,, untuk mengetahui penyusunan properti, serta warna tema yang dipakai pada elemen-elemen dekorasi pernikahan. Mencermati kondisi yang demikian penulis mencoba menganalisis dengan metode analisis deskriptif dan wawancara dengan salah satu wedding organizer di kota Medan. Berdasarkan hasil penelitian ditarik kesimpulan bahwa Kemahen Art Decoration menerapkan prinsip-prinsip desain pada karya dekorasi. Dari beberapa dekorasi ada yang menerapkan semua prinsip desain, dan ada yang menerapkan beberapa prinsip saja. Bentuk yang digunakan banyak menggunakan bentuk-bentuk geometris. Tata letak elemen dekorasi ditata dengan prinsip desain. Serta variasi bentuk dekorasi disesuaikan dengan permintaan dari setiap klien. Namun juga banyak klien meminta jenis dekorasi yang sudah ada disediakan vendor. Kata Kunci: dekorasi, pelaminan, analisis, prinsip, desain.